Rice Growth and Yield Responses to Climate Variabilities and Scenarios - Phuoc, Le Huu; Suliansyah, Irfan; Arlius, Feri; Chaniago, Irawati; Xuan, Nguyen Thi Thanh; Tanh, Nguyen Tran Nhan; Quang, Pham Van (Trends in Sciences, 2022)
Rice is the essential food crop of An Giang Province. Vietnam and the whole world are facing several problems hindering climate change, such as increased temperature and CO2 concentration that many manufacturers’ companies and managers need to estimate output to make production plans or adjust policies. In this study, the model known as SIMPLE was applied to simulate the biomass and yield of rice in 2 crop seasons Autumn - Winter 2020 (AW) and Winter - Spring 2020 - 2021 (WS), in Cho Moi district, An Giang province, Vietnam (10° 23’ 47"N, 105° 27’ 41"E) and analyzed the effects of climate variabilities and scenarios on simulation results. Heat stress showed a relatively negative impact on the growth and development of rice in AW more seriously than WS due to climate variabilities. Climate change scenario RCP8.5 (RCP - Representative Concentration Pathway) has predicted that atmosphere temperature may increase above 4 °C and CO2 concentration to reach 900 ppm by the end of the 21st century. As a result, from the model, for every 100 ppm CO2 concentration increase, the cumulative rice biomass increased by 8 and 10 % in AW and WS, respectively. Moreover, conditions assumed from the model that increased 5 °C caused a decrease in cumulative biomass up to 7.2 % in AW season compared to 3.1 % in WS season. However, with responses of 5 °C increasing in the model, rice yield decreased relatively rapidly from 8.5 % in AW and 7 % WS. HIGHLIGHTS The model known as SIMPLE has been used in this study RMSE of our model differs from the observed yield from 4.2 % (Winter-Spring crop-WS) to 5.5 % (Autumn-Winter crop-AW) For every 100-ppm CO2 concentration increased, the cumulative rice biomass increased by 8 and 10 % in AW and WS, respectively Increasing 5 °C, rice yield decreased 8.5 % in AW and 7 % WS Sensitivity analysis showed that RUE (Radiation Use Efficiency) has the most influencing factor on rice yield GRAPHICAL ABSTRACT